Transcriptomic Variations and Network Hubs Controlling Seed Size and Weight During Maize Seed Development - Wang, Yanzhao; Nie, Lihong; Ma, Juan; Zhou, Bo; Han, Xiaohua; Cheng, Junling; Lu, Xiaomin; Fan, Zaifeng; Li, Yuling; Cao, Yanyong (Frontiers in Plant Science, 2022)
To elucidate the mechanisms underlying seed development in maize, comprehensive RNA-seq analyses were conducted on Zhengdan1002, Zhengdan958, and their parental lines during seven seed developmental stages. We found that gene expression levels were largely nonadditive in hybrids and that cis-only or trans×cis pattern played a large role in hybrid gene regulation during seed developmental stage. Weighted gene co-expression network analysis showed that 36 modules were highly correlated (r = –0.90–0.92, P < 0.05) with kernel weight, length, and width during seed development. Forty-five transcription factors and 38 ribosomal protein genes were identified as major hub genes determining seed size/weight. We also described a network hub, Auxin Response Factor 12 of maize (ZmARF12), a member of a family of transcription factor that mediate gene expression in response to auxin, potentially links auxin signal pathways, cell division, and the size of the seeds. The ZmARF12 mutant exhibited larger seed size and higher grain weight. ZmARF12 transcription was negatively associated with cell division during seed development, which was confirmed by evaluating the yield of protoplasts that isolated from the kernels of the mutant and other inbred lines. Transient knock-down of ZmARF12 in maize plants facilitated cell expansion and division, whereas transient silencing of its potential interactor ZmIAA8 impaired cell division. ZmIAA8 expression was repressed in the ZmARF12 over-expressed protoplasts. The mutant phenotype and the genetics studies presented here illustrated evidence that ZmARF12 is a cell division repressor, and potentially determines the final seed size.